Logics of War Explanations for Limited and Unlimited Conflicts - Weisiger, Alex (Cornell Studies in Security Affairs, 2013)
Most wars between countries end quickly and at relatively low cost. The few in which high-intensity fighting continues for years bring about a disproportionate amount of death and suffering. What separates these few unusually long and intense wars from the many conflicts that are far less destructive? In Logics of War, Alex Weisiger tests three explanations for a nation's decision to go to war and continue fighting regardless of the costs. He combines sharp statistical analysis of interstate wars over the past two centuries with nine narrative case studies. He examines both well-known conflicts like World War II and the Persian Gulf War, as well as unfamiliar ones such as the 1864-1870 Paraguayan War (or the War of the Triple Alliance), which proportionally caused more deaths than any other war in modern history.